A cell culture system developed from heart tissue of the greasy grouper, - Sobhana, K S; George, K C; Venkat Ravi, G; Ittoop, Gijo; Paulraj, R (Indian Journal of Fisheries, 2011)
Heart tissue samples aseptically excised from healthy juveniles of the grouper,Epinephelus tauvina were subjected to enzymaticdissociation using 0.25 % trypsin solution, under aseptic conditions. The resultant cells were suspended in Leibovitz' L-15medium supplemented with 20 % fetal bovine serum. The cells were subsequently seeded into 25 cm2 tissue culture flasks ata density of 106 ml-1 and incubated at 28 Â± 2Â°C. Cells showed spreading and attachment to the culture flasks within 24 h andformed monolayers comprising of epithelioid as well as fibroblast-like cells within 20 days. A confluent monolayer fillingthe flask surface comprising predominantly fibroblastic cells was formed within 30 to 35 days. The cell monolayer washarvested for passage by trypsinisation, which formed successful monolayers in subsequent subcultures.Â